Overview of The Needs of Sustainable Professional Development For Alumni Ners Faculty of Nursing University of Riau - Fitriana Fitriana; Yufitriana Amir; Erwin Erwin (Journal of Nursing Science Update (JNSU), 2021)
Continuing professional development is a process that must be carried out by each individual nurse in order to maintain and update the development of health services through setting high standards of professional practice. The purpose of this research was to determine the need for ongoing professional development activities which include training, seminars, workshops, and formal education for alumni of the Faculty of Nursing, Riau University. Design was descriptive quantitative. The research sample was 293 respondents taken using purposive sampling technique. The results showed the need for continuous professional development in the first priority is training (34.8%) with the type of training needed is emergency nursing training or BTCLS (19.8%), and the second highest priority is formal education (25.3%), who continued S2 if given the opportunity (89.4%) of respondents with the desired form of specialist programs namely management nursing (20.5%) and (10, 6%) want to continue with S3 if given the opportunity. The conclusion of this research is the need for continuing professional development especially training and education activities is very important for Nursing alumni of the Faculty of Nursing, University of Riau to improve their professionalism.Â